Mucoepidermoid carcinoma with metaplastic bone formation—A deceptive radiological presentation. (9th February 2022) - Nel, Chané; Robinson, Liam; van Heerden, Willie F. P.
Abstract: Mucoepidermoid carcinoma (MEC) is one of the most common primary salivary gland malignancies in both children and adults. MECs containing calcifications are rare, but well described in the literature. In contrast, there are only two case reports of MECs showing intra‐tumoural bone formation. MECs associated with calcifications occur more frequently in minor salivary glands, compared to bone formation, which is more commonly seen in major glands. This possibly points to a different pathogenic mechanism. Calcifications of the head and neck region are generally diagnosed on conventional imaging by combining the anatomical location with the pattern of calcification. The radiological findings of MECs containing calcifications or bone formation may mimic benign inflammatory processes such as sialoliths. The purpose of this paper is to report three additional cases of MEC containing metaplastic bone formation. These cases presented as painless swellings with radiological signs that could easily be mistaken for dystrophic calcifications. The clinical relevance of the paper is to make clinicians aware of the deceptive radiological appearance of this entity.